Understand Motivation Perpetrator Action Criminal Murder - Ramadhani, Andi Putri; Rahman, Sufirman; Ulfah, Siti (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze the factors that influence the motivation of perpetrators of murder in Makassar Class I Penitentiary and how psychologists understand the motives behind the behavior of perpetrators of murder. This type of research is empirical legal research, namely research with field data as the main data source, such as interview results. The informants in this study were prisoners and forensic psychologists. The data collection method used literature studies and research by conducting interviews. The results of this study indicate that the factors causing the occurrence of murder are due to internal factors, namely unstable emotional factors, psychology, revenge. External factors are caused by environmental factors, socialization, and economics. The way psychologists understand the motives of perpetrators of murder is by taking a psychological approach and working with law enforcement officers in order to make better decisions based on information provided by psychologists. The recommendation of this research is that prisoners who have been sentenced to prison are expected to use this as a learning experience and be able to control themselves, and also be grateful for what Allah has given, because Allah will not test his servants beyond their capabilities and also forensic psychologists to pay more attention and develop rehabilitation programs for perpetrators of murder.